Retirement plan type and worker mobility - Colleen N. Flaherty Manchester (IZA World of Labor, 2019)
The relationship between retirement plan type and job mobility is more complex than typically considered. While differences in plan features and benefit structure may directly affect employees' mobility decisions (“incentive effect”), the type of plan offered may also affect the types of employees a given employer attracts (“selection effect”), thereby affecting mobility through a second, indirect channel. At the same time, some employees may not be able to accurately assess differences between plan types due to limited financial literacy. These factors have implications for policymakers and employers considering retirement plan offerings.
Keywords: J26; J32; J6; J62; 330; retirement plans; job mobility; worker transitions